Morphometric wing variations in Fischer’s lovebirds (Agapornis fischeri) related to sex and age at 4–6 months - Yeni Dhamayanti; Ilyasa Adzani; Muhammet Bayram; Lintang Winantya Firdausy (Jurnal Medik Veteriner, 2026)
Wing morphometry plays a crucial role in avian functional ecology, influencing flight performance, energy efficiency, and sexual selection. However, quantitative data on wing development in lovebirds (Agapornis fischeri), remain scarce. This study aimed to quantify and compare the growth of wing flexion width, wing extension width, and wingspan in male and female lovebirds at 4, 5, and 6 months of age to determine the onset and extent of sexual dimorphism. A total of 22 lovebirds (11 males and 11 females) were acclimatized under controlled environmental conditions and fed a millet-based diet. Wing measurements were obtained in accordance with animal welfare protocols using standardized morphometric techniques. Data were analyzed using Multivariate Analysis of Variance (MANOVA) followed by Tukey’s post hoc test at a 95% confidence level, and growth patterns were evaluated using linear regression analysis. Results showed significant (p < 0.05) sex- and age-related differences in all morphometric parameters. Males exhibited consistently higher mean values for wing flexion, extension, and wingspan at every age, with steeper linear growth slopes compared with females. The steady, positive correlation between age and wing dimensions indicates continuous and proportional development during the juvenile phase. These findings suggest that sexual dimorphism in wing morphology becomes evident as early as four months of age and intensifies with maturation. This study provides baseline trajectories of wing morphometrics in lovebirds, establishing reference standards that are valuable for avian biology, welfare, and sexing applications in psittacine species.